The Role of Law Enforcement Officers in Handling Domestic Violence Cases in the Southeast Aceh Police Criminal Investigation Unit - Zubaidah; Rahmayanti; Suci Ramadani (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
-Domestic Violence (KDRT) is a criminal act that has a serious impact on the victim, both physically, psychologically, and socially. Case data in the jurisdiction of the Southeast Aceh Police shows an increase in the number of domestic violence cases from 2020 to 2024. This increase indicates that there is still low public legal awareness, strong patriarchal cultural factors, and an inoptimal victim protection system. This study formulates problems regarding the obstacles faced by law enforcement officials, legal efforts carried out, and the role of law enforcement officials in handling domestic violence cases in the Southeast Aceh Police Criminal Investigation Unit. The purpose of this research is to analyze obstacles, examine the form of legal remedies, and assess the effectiveness of the role of law enforcement officials based on the provisions of applicable laws and regulations. The research method used is empirical normative legal research with a legislative approach and a case approach, supported by domestic violence case data in the last five years. The results of the study show that obstacles to handling domestic violence include limited facilities and infrastructure, limited human resources, low victim participation in the legal process, and socio-cultural factors of the community. Legal remedies carried out by law enforcement officials include preventive, repressive, and combined measures in accordance with the provisions of Law Number 23 of 2004 and the criminal procedure law. The role of law enforcement officials is a determining factor in ensuring victim protection and the effectiveness of law enforcement. Thus, it is necessary to strengthen institutional capacity, increase the professionalism of the apparatus, and increase public legal awareness in order to realize fair and victim-oriented domestic violence law enforcement.